2020
DOI: 10.1111/mpp.12974
|View full text |Cite
|
Sign up to set email alerts
|

Alpha‐momorcharin enhances Nicotiana benthamiana resistance to tobacco mosaic virus infection through modulation of reactive oxygen species

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 80 publications
1
25
0
Order By: Relevance
“…Our model indicates that viral infection results in an increase in the expression of γ‐glutamylcysteine synthetase and GSH synthetase, which promote GSH biosynthesis, and are necessary for SA accumulation, downstream signalling processes, and ROS scavenging‐related genes activation (Figure 8 ). Increasing evidence indicates that an early ROS burst, followed by suppression of ROS, is a requirement for successful resistance of plants to TMV and other viruses (Balasubramaniam et al, 2014 ; Király et al, 2008 ; Shang et al, 2019 ; Zhu et al, 2020 ). Overall, in N. benthamiana GSH is essential for both local and systemic resistance against TMV infection through a differential modulation of SA signalling and ROS, possibly acting as the initiating signals for systemic resistance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our model indicates that viral infection results in an increase in the expression of γ‐glutamylcysteine synthetase and GSH synthetase, which promote GSH biosynthesis, and are necessary for SA accumulation, downstream signalling processes, and ROS scavenging‐related genes activation (Figure 8 ). Increasing evidence indicates that an early ROS burst, followed by suppression of ROS, is a requirement for successful resistance of plants to TMV and other viruses (Balasubramaniam et al, 2014 ; Király et al, 2008 ; Shang et al, 2019 ; Zhu et al, 2020 ). Overall, in N. benthamiana GSH is essential for both local and systemic resistance against TMV infection through a differential modulation of SA signalling and ROS, possibly acting as the initiating signals for systemic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation level of H 2 O 2 was observed using DAB as described previously (Zhu et al, 2020 ). Endogenous H 2 O 2 concentrations were determined according to the protocol described by Chen et al ( 2019 ) using a hydrogen peroxide assay kit (Solarbio) (Chen et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Redox homeostasis plays an essential role in plant immunity against viruses [ 44 , 45 , 46 ]. A significant increase of ROS content in leaf was reported in a susceptible genotype but not in a tolerant genotype of barley infected with barley yellow dwarf virus [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, different results have been obtained depending on the RIP studied and the approach used. Thus, it has been reported that α-momorcharin (α-MMC), in N. benthamiana plants sprayed with a solution of the RIP, up-regulates the expression of reactive oxygen species (ROS) scavenging-related genes, modulating ROS homeostasis and conferring resistance to TMV, ChiVMV, and CMV infection [ 81 , 133 ]. Additionally, this RIP also up-regulates some salicylic acid-responsive defence-related genes [ 81 ].…”
Section: Antiviral Mechanisms Of Ripsmentioning
confidence: 99%